Inventarisasi dan Identifikasi Tumbuhan Famili Cyperaceae di Sekitar Laboratorium Terpadu UIN Sunan Gunung Djati Bandung - Riana Qodariah Hasanah; Rini Rini; Ateng Supriyatna (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The Cyperaceae family is a puzzle or "papayungan" family. The Cyperaceae family are weeds because they can grow in different environmental conditions. Many species of this family grow in terrestrial and near-water ecosystems. Plant inventory is an activity that aims to classify a plant species found in an area. This activity is carried out to provide information which is used as a reference for the species of this family that exist in the area, with the aim of knowing the distribution of the species of this family and identifying them. This observation uses the exploration method around the UIN Sunan Gunung Djati Bandung Integrated Laboratory. The Cyperaceae family around the UIN Sunan Gunung Djati Bandung Integrated Laboratory obtained 3 species, namely the species Cyperus rotundus L, Cyperus kyllingia Endl, and Fimbristylis globulosa.